PENERJEMAHAN KARYA SASTRA ANAK: SEBUAH TINJAUAN TEORETIS - Rachmawati, Raja (Kementerian Sekretariat Negara Republik Indonesia, 2014)
The topic of this article is the translation of children's literature, particularly as it pertains to the application of translation theory. The article discusses children's literature, the aims of children's literature translation, the culture influencing children's literature translation, and the challenges in the translation of children's literature that consist of the adaption of cultural contexts, the modification of cultural values, the translator's understanding of child readers of children's literature, the difficulty of languages and language styles and the readers characteristics. Based on the discussion, it can be concluded that thetranslation of children's literature is not an easy task for a translator due to the fact that a translator does not only translate the language but must also adapt and adjust to the different cultures of both thesource and target languages. Besides, the children's reading of translated literature books aims to make them cultivate an open mind on their future world, develop their sense of humanity and environment in other countries, and learn foreign languages.